Urban–rural differences in health literacy and its determinants in Iran: A community‐based study. (6th December 2017) - Golboni, Farzaneh; Nadrian, Haidar; Najafi, Sarisa; Shirzadi, Shayesteh; Mahmoodi, Hassan
Abstract: Objective: Previous studies have shown a remarkable difference in functional health literacy among residents of urban and rural areas which may be attributed to socioeconomic inequalities between these areas. The aim of this study was to investigate the differences (if any) in the level of functional health literacy and its determinants between urban and rural areas in Sanandaj, Iran. Design: A descriptive analytical cross‐sectional study. Participants: A multistage clustered random sample of 1000 respondents older than 18 years. In total, 892 respondents (response rate = 89.2%) completed test of functional health literacy in adults questionnaire through personal home‐based interviews. Applying SPSS v. 16, a series ofanova, t ‐test and logistic regression tests were conducted. Main outcome measures: Inadequate/marginal functional health literacy. Results: Respondents residing in rural areas having a diploma education and lower, with no history of hospitalisation, with monthly income <US$ 165 and being diagnosed with a chronic disease had significantly higher rates of inadequate/marginal functional health literacy. Among rural, but not urban, residents having a history of hospitalisation, a university education and a higher monthly income increased the odds of adequate functional health literacy by 1.84, 2.29 and 1.95 times, respectively. Conclusions: The rural area residents suffered more from low functional health literacy, compared with their urban counterparts. Health literacy as a determinant of health and social welfare should be focused on with more detail by health decision‐makers.